Pertunjukan Wayang Dalam Era Global - SOETARNO - (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2008)
Shadow Puppet Performances in Global Era. This article discusses the changes of shadow puppetry inrelation to the changes of society in global era. Some relevant changes are in the fi elds of: (a) communicationtechnology; (b) social systems; and (c) value systems. To anticipate these changes, puppet masters have also madesome changes in their performances. The shadow puppet performances and society cannot stand alone but theyhave mutual interactions. Each of them may act as an object or as a subject. Thus, in transitional or developingsociety, the infl uences of social and shadow puppetry are mutual. Shadow puppet performances reveal socialtendencies while society show infl uences on the development of shadow puppetry world.